Single-Stage Combined Embolization and Resection for Spetzler-Martin Grade III/IV/V Arteriovenous Malformations: A Single-Center Experience and Literature Review - Chen, Yu; Li, Ruinan; Ma, Li; Zhao, Yang; Yu, Tengfei; Wang, Hao; Ye, Xun; Wang, Rong; Chen, Xiaolin; Zhao, Yuanli (Frontiers in Neurology, 2020)
Background and Purpose: This study sought to identify the efficacy and intraoperative operational details of single-stage combined embolization and microsurgery strategy for Spetzler-Martin (SM) grade III/IV/V arteriovenous malformations (AVMs). Methods: The authors retrospectively reviewed consecutive SM grade III/IV/V AVMs who underwent hybrid procedures and surgical resection alone procedures from January 2016 to February 2018. Outcomes (modified Rankin Scale [mRS]) were compared between hybrid group and surgical resection alone group in ruptured or unruptured subgroup. Factors associated with long-term disability were assessed using multivariable logistic regression analyses. Results: A total of 100 AVM patients (47 corrected using hybrid procedures whereas 53 by surgical resection alone) were evaluated. After a mean follow-up of 2.3±0.6 years, we found no difference in long-term prognosis and incidences of disability rates between these two strategies. However, the hybrid strategy offers significant advantage in accelerating the resection process (ruptured, [P=0.000]; unruptured, [P=0.002]). In the analysis of risk factors, excessive embolization (Grade C, 60%-100%) was significantly associated with long-term disability in the hybrid cohorts (P=0.041; odds ratio, 24.000; 95%CI, 1.140-505.194), and involvement of deep perforating arteries was the significant predictor of long-term disability in the surgical resection alone cohort (P=0.025; odds ratio, 15.389; 95%CI, 1.412-167.66). In the subgroup analysis of the hybrid cohort, moderate embolization (Grade B, 30%-60%) was recommended because of the low risk ratio of major intraoperative bleeding (P=0.033). Conclusions: Single-stage combined embolization and resection is an efficient strategy for the treatment of SM grade III/IV/V AVMs. Although the long-term outcomes were similar to surgical resection alone, the hybrid strategy had obvious advantages of shorter resection. In the hybrid technique, moderate embolization was recommended, and excessive embolization might be detrimental to the subsequent microsurgical resection.